Reducing learning boredom learning plateau through group guidance intervention using gestalt approach with staying with feelings technique: A quasi-experimental study on high school students - Pratiwi, Hanifah; Firman, Firman; Ardi, Zadrian (Universitas Negeri Padang, 2024)
This study determines the effect of group guidance intervention using the Gestalt approach with a fixed technique with feelings on students' learning plateau. This study used a quasi-experimental research design with a pretest posttest control group design. The population in this study were 547 students in class XI at SMAN 3 Padang and then selected with certain criteria as many as two classes as experimental classes and control classes, namely class XI I and XI II with a total of 64 students. Sample withdrawal used simple random sampling. It is taken 20 students who are divided into 10 students for the experimental group and 10 students for the control group. The research instrument used a Likert scale model. Data were collected at two different times, namely pretest and posttest. Data analysis techniques used Wilcoxon Signed ranks Test and Kolmogorov Smirnov.Based on the results of research and discussion, it is concluded that group guidance services using the Gestalt approach with a fixed technique with feelings can reduce students' learning plateau at school. Therefore, it is recommended that high schools need to maximize the implementation of group guidance in schools to help reduce students' learning plateau. Therefore, it is recommended that school counselors and advisors use this technique more frequently in group counseling sessions. This technique encourages students to become more aware of and express their feelings, which can help them cope with stress and academic pressure, ultimately assisting students in overcoming their learning burnout